The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0097172
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in ABC Transporter Genes and Concentrations of Mercury in Newborns – Evidence from Two Mediterranean Birth Cohorts

Abstract: BackgroundThe genetic background may influence methylmercury (MeHg) metabolism and neurotoxicity. ATP binding cassette (ABC) transporters actively transport various xenobiotics across biological membranes.ObjectiveTo investigate the role of ABC polymorphisms as modifiers of prenatal exposure to MeHg.MethodsThe study population consisted of participants (n = 1651) in two birth cohorts, one in Italy and Greece (PHIME) and the other in Spain (INMA). Women were recruited during pregnancy in Italy and Spain, and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 29 publications
1
28
0
2
Order By: Relevance
“…10 Llop et al found an association of the ABC-transporters ABCB1, ABCC1 and ABCC2 and mercury accumulation in the fetus. 35 A number of transporters are described for the choroid plexus. 36 Among these, we selected the OATs and MRPs as well as P-gp (ABCB1) and the breast cancer resistance protein (BCRP, ABCG2) for first inhibition experiments (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…10 Llop et al found an association of the ABC-transporters ABCB1, ABCC1 and ABCC2 and mercury accumulation in the fetus. 35 A number of transporters are described for the choroid plexus. 36 Among these, we selected the OATs and MRPs as well as P-gp (ABCB1) and the breast cancer resistance protein (BCRP, ABCG2) for first inhibition experiments (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…TagSNPs were selected according to HapMap data (Thorisson et al 2005) for YRI (Yoruba in Ibadan, Nigeria) as a proxy for African populations, since earlier screenings of this population have shown that the allele frequencies are more similar to YRI than the other Hapmap populations (Yeates et al 2015). In total, we genotyped 15 SNPs (description of all SNPs is found in Table 1) including the three SNPs that previously had been linked to cord blood Hg in Mediterranean cohorts: ABCC1 rs11075290, ABCC2 rs2273697, and ABCB1 rs2032582 (Llop et al 2014). ABCB1 rs2032582 is tri-allelic and was genotyped by two different TaqMan assays to capture all three alleles.…”
Section: Methodsmentioning
confidence: 99%
“…The role of ABC transporters in MeHg transport suggests that single nucleotide polymorphisms (SNPs) in ABC transporters may influence MeHg body burden in both mother and fetus during pregnancy. Indeed, in a study based on two European birth cohorts, it was found that child SNPs in ABCC1, ABCC2 , and ABCB1 modified the relationship between maternal fish consumption and cord blood Hg concentrations (Llop et al 2014). However, it is not known whether ABC SNPs influence the concentration of maternal hair Hg, a biomarker often used as a proxy for prenatal exposure to MeHg (Davidson et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have explored genetic predisposition and nutritional modifiers as factors that confer tolerance or susceptibility to MeHg among populations and in individuals [9][11]. In addition to neurotoxicity, recent population studies have identified MeHg effects on cardiovascular factors (e.g., heart rate variability and blood pressure) [12], [13] and the immune system [14], [15].…”
Section: Introductionmentioning
confidence: 99%